2016
DOI: 10.1007/s00586-016-4454-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic measurement for transforaminal percutaneous endoscopic approach (PELD)

Abstract: At lower lumbar levels the exiting nerve root is at risks of injury. Hence, it is advised to enlarge the foramen for safe passage of endoscopic instruments and to minimize the possibility of nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 26 publications
11
38
0
Order By: Relevance
“…Our group measured the distance from the nerve root to the lateral border of the superior facet on the MRI axis in the superior and inferior margins of the intervertebral disc. From the L 2‐3 level to the L 5 S 1 level, the maximum value is 6.41 mm. In this study, the distance from the exiting nerve root to the facet joint surface, which is equivalent to the removal of the entire superior articular process during surgery, on the CT axis was larger on the inferior margins of the disc.…”
Section: Discussionmentioning
confidence: 53%
“…Our group measured the distance from the nerve root to the lateral border of the superior facet on the MRI axis in the superior and inferior margins of the intervertebral disc. From the L 2‐3 level to the L 5 S 1 level, the maximum value is 6.41 mm. In this study, the distance from the exiting nerve root to the facet joint surface, which is equivalent to the removal of the entire superior articular process during surgery, on the CT axis was larger on the inferior margins of the disc.…”
Section: Discussionmentioning
confidence: 53%
“…Previous reports documented attempts at evaluating the triangular working zone on transverse, sagittal, and coronal MR images. 6,9,10,27 Examinations of nerve root branching angles in MR coronal images showed that the intervertebral disk angles are smaller in the lower spinal column intervertebral spaces. 10 Further, some studies evaluated distances between SAPs and exiting nerves and measured these distances on MR transverse images at the inferior intervertebral disk margins.…”
Section: Discussionmentioning
confidence: 99%
“…10 Further, some studies evaluated distances between SAPs and exiting nerves and measured these distances on MR transverse images at the inferior intervertebral disk margins. 8,10,27 These values may make it possible to determine the increased surgical risk in patients with small triangular working zones, although there are a limited number of reports on clinical outcomes in patients who were considered to be at low risk. 6 However, in all of these studies, the authors revealed that because the triangular working zone is a 3D structure, there are limitations to evaluating it on 2D images.…”
Section: Discussionmentioning
confidence: 99%
“…Since the body sizes of individual patients are different, the puncture and localization procedures mainly rely on the experience of the operators, making it one of the most difficult steps for beginners in performing PELD (13). The existing preoperative measuring methods mainly rely on 2-dimensional (2D) X-ray images or MRI cross-sections (14). Because the bony structure and the trajectory are 3-dimensional (3D), the relationship between the anatomical lumbar structure and the working channel cannot be evaluated precisely.…”
Section: Virtual Trajectory Placement and Measurementmentioning
confidence: 99%